Herramienta para la medición del desempeño de los requisitos del SGC, considerando criterios normativos ISO (2022)
ED performance evaluation for QMS - quality management systems - is a widely discussed topic, aimed at measuring the degree to which planned results are achieved. However, there is very limited information on mechanisms or methodologies to evaluate the degree of compliance with ISO 9001:2015 requirements. Because the audit process is in charge of evaluating compliance with quality requirements dichotomously (compliant and non-compliant), this does not allow the gaps between the current state of the requirement and the expected result to be evidenced. In this sense, with this quantitative research, developed from a descriptive design study, a tool was designed for the DE of a QMS, based on normative criteria of different ISO documents, to provide a basis for companies that want to accurately and quantitatively measure the degree of to which the requirements of the ISO 9001:2015, PHVA cycle framework are being met and where the strengths and weaknesses of the system can be clearly and simply identified.